Changes in temperature alter competitive interactions and overall structure of fig wasp communities. Issue 6 (24th April 2022) - Aung, Khin Me Me; Chen, Huan‐Huan; Segar, Simon T.; Miao, Bai‐Ge; Peng, Yan‐Qiong; Liu, Cong
Abstract: Organisms exist within ecological networks, connected through interactions such as parasitism, predation and mutualism which can modify their abundance and distribution within habitat patches. Differential species responses make it hard to predict the influence of climate change at the community scale. Understanding the interplay between climate and biotic interactions can improve our predictions of how ecosystems will respond to current global warming. We aim to understand how climate affects the multitrophic biotic interactions as well as the community structure using the enclosed communities of wasps associated with figs as study system. To examine the presence and strength of multitrophic species interactions, we first characterized the multitrophic community of fig wasps associated with Ficus racemosa and then applied hierarchical joint species distribution models, fitted to community monitoring data. We further evaluated the effect of climate on individual species trends as well as interspecific interactions. We found that the competitive balance shifted to favour non‐pollinating galling wasps and disadvantage the dominant pollinator in suboptimal conditions. Furthermore, suboptimal conditions for galling wasps facilitated the occurrence of their specialized parasitoid, as changes cascaded across trophic levels and led to alternative community structures. Our results highlight the role of how species interactions can be modified across multiple trophic levels in a fig wasp community according to climate. Abstract : By investigating the responses of fig wasp species to temperature shifts, this study highlights the central role of biotic interactions in determining the impact of climate on ecological communities. 摘要: 生态系统中的各类生物通过寄生、捕食、互惠等相互作用组成生态网络，并相互影响与制约。由于不同物种外界变化的响应存在差异，在群落水平上预测气候变化对生物的影响一直是个难点。了解气候与物种间相互作用怎样共同作用于群落中的物种，有助于完善生态系统如何响应当前气候变暖的预测。 在该研究中，我们选用榕小蜂群落作为研究系统，目标揭示气候怎样影响多营养级生物互作体及其群落结构。 我们首先通过应用层级联合物种分布模型 (Hierarchical joint species distribution models) 分析了群落监测数据，检测了聚果榕多营养级榕小蜂群落多种种间互作的关系与强度。再进一步评估气候对单个物种动态及种间互作的影响。 研究发现:当处于非最佳气候条件时，同一营养级之间的种间竞争更倾向于非优势的非传粉造瘿小蜂，对优势的传粉榕小蜂不利；而且同一营养级之间竞争平衡的倾斜，通过跨营养级的级联效应促进了非传粉造瘿小蜂专性复寄生蜂的发生，从而导致群落结构的改变。结果强调了气候通过级联效应影响种间的不同互作关系，最终影响多营养级的榕小蜂群落。